“Bridging the digital gap”: Students’ awareness, ease of use, and self-efficacy towards online learning among university students in Nigeria - Hamzat, Afeez Abiola (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2025)
The integration of online learning applications has become an indispensable innovation in 21st-century education. Platforms such as Zoom, Google Classroom, Microsoft Teams, and Canvas have facilitated internet-based learning, especially during the COVID-19 pandemic. However, the extent to which students adopt and effectively use these tools remains uneven. This study investigated undergraduate students’ awareness, perceived ease of use, and self-efficacy in using online learning applications across universities in Oyo State, Nigeria. A descriptive survey design was employed, involving 270 undergraduate students selected through simple random sampling from three purposively chosen universities. Data were collected using a researcher-designed questionnaire, validated and tested for reliability (Cronbach’s Alpha = 0.76). Descriptive statistics (mean scores) and inferential statistics (independent sample t-test) were used for data analysis. Findings revealed that students’ awareness of online learning applications was high (M = 2.64), and their perceived ease of use was positive (M = 2.63). However, their self-efficacy in using these applications was low (M = 1.90), indicating a gap between recognition and confident usage. This suggests that despite being familiar with digital platforms, many students still lack the confidence and skills needed to navigate them effectively. No significant gender difference was found in students’ self-efficacy levels (p = .42, p > .05). The study concludes that while awareness and perceived usability are encouraging, students' confidence in using online learning tools remains inadequate. It recommends enhanced access to digital infrastructure and targeted capacity-building workshops to improve self-efficacy and maximize the benefits of online learning.